2016
DOI: 10.1200/jco.2015.63.9898
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Radiation Oncologist Experience Among Patients With Head-and-Neck Cancer Treated With Intensity-Modulated Radiation Therapy

Abstract: Patients receiving IMRT for HNC had improved outcomes when treated by higher-volume providers. These findings will better inform patients and providers when making decisions about treatment, and emphasize the critical importance of high-quality radiation therapy for optimal treatment of HNC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
115
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 24 publications
7
115
2
Order By: Relevance
“…An increasing amount of data supports the hypothesis that radiation therapy by high-volume providers is associated with improved outcomes in HNC [13,14] and multiple non-HNC malignancies like lung, cervical, and prostate cancers [15][16][17][18]. In HNC, two recent large national database analyses have noted disparities in access to high-volume providers, which may serve as another proxy for access to high-quality cancer care.…”
Section: Evidence Of Radiation Therapy Delivery Disparities In Hncmentioning
confidence: 97%
See 1 more Smart Citation
“…An increasing amount of data supports the hypothesis that radiation therapy by high-volume providers is associated with improved outcomes in HNC [13,14] and multiple non-HNC malignancies like lung, cervical, and prostate cancers [15][16][17][18]. In HNC, two recent large national database analyses have noted disparities in access to high-volume providers, which may serve as another proxy for access to high-quality cancer care.…”
Section: Evidence Of Radiation Therapy Delivery Disparities In Hncmentioning
confidence: 97%
“…In HNC, two recent large national database analyses have noted disparities in access to high-volume providers, which may serve as another proxy for access to high-quality cancer care. First, Boero et al found that in the SEERMedicare linked database, white patients receiving 3D-conformal radiation therapy and intensity-modulated radiation therapy for HNC were more significantly likely to be treated by high-volume radiation oncologists than non-white patients [13]. Second, Wuthrick et al reported that patients with private insurance were more likely to receive HNC treatment at highaccruing facilities into Radiation Therapy Oncology Group trials than those without private insurance [14].…”
Section: Evidence Of Radiation Therapy Delivery Disparities In Hncmentioning
confidence: 99%
“…We identified the treating radiation oncologist (provider) using previously described methods (25). Briefly, we identified the specific provider using the Unique Physician Identification Number (UPIN) or National Physician Identifier (NPI) associated with the provider-specific weekly management code 77247.…”
Section: Radiation Therapy and Providermentioning
confidence: 99%
“…Grit, motivation, reputation, and integrity are the types of personal qualities that will prove elusive for any big data approach. Finally, it would be interesting to determine if high volume physicians had better outcomes than lower volume physicians as demonstrated in previous studies [27].…”
Section: Discussionmentioning
confidence: 91%